Commemorative plaque, Port Trust War Memorial - Ghosh, Ayan (2023)
The development of Ballard Estate coincided with the outbreak of World War I (1914-18) in which India sent troops on behalf of the British Empire. The Port Trust War Memorial records the significant contribution of the Port of Bombay in WWI. It mentions the passage of 18,70,000 troops and personnel through the docks to different theatres of the war. The first transport left Bombay on August 21, 1914.